2011
DOI: 10.2106/jbjs.j.00039
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Infection Following Posterior Lumbar Instrumented Arthrodesis

Abstract: This analysis confirms previously demonstrated risk factors for postoperative infection while reporting on new potential independent risk factors of osteoporosis, chronic obstructive pulmonary disease, and dural tears in the setting of posterior lumbar instrumented arthrodesis. Areas of new research can focus on the roles these novel factors may play in the pathogenesis of surgical site infections in the spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(184 citation statements)
references
References 24 publications
10
167
1
6
Order By: Relevance
“…Furthermore, moderate significant heterogeneity was observed between studies of the unadjusted risk estimate. Influence analysis showed that this heterogeneity was mostly due to the high OR reported by Koutsoumbelis et al [26]. However, after adjusting for confounders, the study's results approximated those from other studies.…”
Section: Odds Ratiomentioning
(Expert classified)
See 2 more Smart Citations
“…Furthermore, moderate significant heterogeneity was observed between studies of the unadjusted risk estimate. Influence analysis showed that this heterogeneity was mostly due to the high OR reported by Koutsoumbelis et al [26]. However, after adjusting for confounders, the study's results approximated those from other studies.…”
Section: Odds Ratiomentioning
(Expert classified)
“…Five additional potentially relevant studies were identified from reference lists. Of the 34 articles that underwent full-text review, 12 [22][23][24][25][26][27][28][29][30][31][32][33] met eligibility criteria for inclusion in the meta-analysis and 22 were excluded. The most common reasons for exclusion of the 22 studies were: criteria for the diagnosis of SSI not reported and/or CDC/NNIS criteria not applied [34][35][36][37][38][39][40][41][42][43][44][45][46][47], non-scalar definitions of obesity used [47][48][49], risk estimates of the association between obesity/BMI and SSI not reported or raw data not provided to calculate risks [44,47,[50][51][52][53], and analyses restricted to deep wound infections [54,55].…”
Section: Literature Search and Systematic Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous variables analyzed includes patient's age, body mass index (BMI), length of operation, duration of hospitalization, number of intervertebral levels operated on, preoperative glucose levels, and estimated blood loss. These risk factors were chosen based on the previous literature evaluating SSI in spinal surgeries [7,10,11,16].…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, patients who are obese may have difficulties with surgical access and there have been reports of an increased risk of operative complications for surgical procedures such as spinal surgery [4,6,8,17,22,23,29,35]. Some studies reported that obesity has been associated with unfavorable surgical outcomes such as longer operative times, greater operative blood loss, and a higher rate of revision for patients having spinal surgery [10,14,31,32,35,39].…”
Section: Introductionmentioning
confidence: 99%